Reduction and retention of thoracolumbar fractures by minimally invasive stabilisation versus open posterior instrumentation. (October 2015) - Fitschen-Oestern, Stefanie; Scheuerlein, Florian; Weuster, Matthias; Klueter, Tim; Menzdorf, Leif; Varoga, Deike; Kopetsch, Christoph; Mueller, Michael; van der Horst, Alex; Seekamp, Andreas; Behrendt, Peter; Lippross, Sebastian
Abstract: Purpose: The purpose of this study was in thoracolumbar fractures to assess the effectiveness of minimal invasive stabilisation compared to the open technique with regards to the change in kyphosis angle, the loss of reduction and length of hospital stay. Methods: The retrospective study consisted of 104 patients who received minimally invasive stabilisation or open stabilisation. Patients were between 15 and 86 years of age, had a thoracolumbar fracture and no neurological deficits. Kyphotic angle (Cobb angle) and loss of reduction was compared after minimal invasive and open stabilisation. The Cobb angle was evaluated directly post operatively, at 6 weeks, 3 months, 6 months and 12 months after surgery. Results: Evaluated patients who received the minimally invasive technique had a shorter surgical intervention time and a shorter hospital stay compared to patients who received the open technique. Kyphosis angle and loss of reduction showed no significant difference compared to open technique. There was also no significant difference between minimally invasive poly-axial and mono-axial stabilisation. Conclusion: In this study we provide evidence that MIS instrumentation in selected thoracolumbar fractures can effectively be used without significant differences in loss of reduction compared to open stabilisation. MIS can also sufficiently retain reduction as compared to traditional open techniques. The main advantages are reduced operation time and shorter hospital stay.